2005
DOI: 10.1021/jp056386n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Determination of Multiple Exchange Couplings and Magnetic Susceptibility Data in Inorganic Solids:  The Prototypical Case of Cu2(OH)3NO3

Abstract: Density functional theory based on hybrid functionals and localized atomic type basis sets is employed to calculate the exchange couplings in the layered three-dimensional compound Cu2(OH)3NO3. We assign accurate values to the six different in-plane exchange couplings. Interlayer exchange interactions through hydrogen bonds are also quantified. The calculated exchange coupling constants are then employed to perform quantum Monte Carlo simulations to yield magnetic susceptibility data, which compare successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
8
35
0
Order By: Relevance
“…The Peintinger-Oliveira-Bredow split-valence triple-ζ (pob-TZVP) basis sets (Peintinger et al 2013) were used for all atoms along with the hybrid Becke-3-Lee-Yang-Parr (B3LYP) functional, which provides excellent results for copper oxysalt crystals (Ruiz et al 2006;Ruggiero et al 2015;Krivovichev et al 2016a, b). Geometry optimization was initiated with experimental determined crystal-structure models determined for clinoclase and gilmarite by Eby and Hawthorne (1990) and Sarp and Černý (1999), respectively (Tab.…”
Section: Density Functional Theory (Dft) Modelingmentioning
confidence: 99%
“…The Peintinger-Oliveira-Bredow split-valence triple-ζ (pob-TZVP) basis sets (Peintinger et al 2013) were used for all atoms along with the hybrid Becke-3-Lee-Yang-Parr (B3LYP) functional, which provides excellent results for copper oxysalt crystals (Ruiz et al 2006;Ruggiero et al 2015;Krivovichev et al 2016a, b). Geometry optimization was initiated with experimental determined crystal-structure models determined for clinoclase and gilmarite by Eby and Hawthorne (1990) and Sarp and Černý (1999), respectively (Tab.…”
Section: Density Functional Theory (Dft) Modelingmentioning
confidence: 99%
“…[27] Triple-z and double-z all-electron basis sets proposed by Ahlrichs et al were used for the metal and for the rest of the atoms, respectively. [28,29] The broken symmetry approach was employed to describe the unrestricted solutions of the antiferromagnetic spin states, [30] which were obtained from the guess functions generated with the fragment tool implemented in the Gaussian code. The full geometry was used for [Cu 3 A C H T U N G T R E N N U N G (pyr)A C H T U N G T R E N N U N G (m 3 -CO 3 )]·A C H T U N G T R E N N U N G (ClO 4 ) 4 ·H 2 O. DF calculations were also performed on a dinuclear model in which the copper(II) ions were perfectly placed in the carbonate plane and, to allow close positions for the metal atoms, the peripheral ligands were placed in a plane perpendicular to that built from the carbonate group.…”
Section: Esi-msmentioning
confidence: 99%
“…In a recent paper, [43] Ruiz et al calculated the value of J between Cu II with several different Cu···O···Cu angles and Cu···Cu distances and concluded that a decrease of the Cu···O···Cu angle weakens the antiferromagnetic Cu···Cu interactions when such angles are larger than about 100°i n spite of the antiferromagnetic contributions due to the decrease of the Cu···Cu distance. We can see the same from Table 2, which only gives the results calculated using the PW91 functional, namely that the decrease of the Cu···O···Cu angle weakens the antiferromagnetic Cu···Cu interactions in spite of the decrease of the Cu···Cu distance when the diamagnetic central ions are La III .…”
Section: Effects Of the Structural Parameters On The Interactions Betmentioning
confidence: 99%